Health insurance and health environment: India's subsidized health insurance in a context of limited water and sanitation services - Florence McBain (University of Bonn, Center for Development Research (ZEF), 2014)
Recently, many emerging countries have established subsidized health insurance schemes to provide financial protection and support access to health care to poor households. The challenge to ensure the long term sustainability of such schemes is huge. In this paper, the impact of the health environment on the long term sustainability of a health insurance is explored, focusing on water and sanitation. India offers an interesting case to explore this question. Indeed, since 2008 India launched a fully subsidized health insurance Rashtriya Swasthya Bima Yojana (RSBY) in a context where 56% of its population does not have access to safe sanitation and 8% do not have access to safe water (JMP, 2012). A framework is proposed linking water supply and sanitation; health status of the insured population; health insurance and the productivity of households. Next, based on a literature review, the outcomes of investments in water and sanitation and health insurance are reviewed and the potential synergies and trade-offs of combing these investments are explored. In a last section, the case of India is analysed in detail, with international comparisons and further research lines are proposed.
Keywords: 330; Health insurance; financial sustainability; water and sanitation; India